2021
DOI: 10.1007/s12144-021-02000-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of preservice teachers’ implicit attitudes and causal attributions: a deeper look into students’ ethnicity

Abstract: Previous research has provided evidence that teachers implicitly hold more negative attitudes toward ethnic minority students than toward ethnic majority students. Furthermore, they attribute the lower educational success of ethnic minority students predominantly to internal causes. So far, it is not known how implicit attitudes and causal attributions are related to preservice teachers’ judgments of students’ academic competencies. We conducted a study to close this research gap. In a sample of preservice tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 81 publications
(105 reference statements)
1
6
2
Order By: Relevance
“…Internal stable attributions of low success in school and more negative implicit attitudes led to lower language performance ratings. The internal attributions are in line with previous research ( Froehlich et al, 2016 ; Glock and Kleen, 2021 ), but the separate consideration of internal variable and internal stable attributions is new and is especially interesting as previous research showed that ethnic minority students’ language problems were often attributed to low effort ( Agirdag et al, 2014 ) and thus to internal variable attributions. In the current study, the preservice teachers attributed the ethnic minority student’s German language proficiency to the student’s ability.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Internal stable attributions of low success in school and more negative implicit attitudes led to lower language performance ratings. The internal attributions are in line with previous research ( Froehlich et al, 2016 ; Glock and Kleen, 2021 ), but the separate consideration of internal variable and internal stable attributions is new and is especially interesting as previous research showed that ethnic minority students’ language problems were often attributed to low effort ( Agirdag et al, 2014 ) and thus to internal variable attributions. In the current study, the preservice teachers attributed the ethnic minority student’s German language proficiency to the student’s ability.…”
Section: Discussionsupporting
confidence: 85%
“…Based on this model, teachers’ implicit attitudes toward ethnic minority students as well as their causal attributions regarding ethnic minority students’ achievements may play an important role in ethnic minority students’ disadvantages in school. Concurrent with this assumption, research showed that preservice teachers with more negative attitudes toward ethnic minority students and a tendency to attribute academic failure to internal stable factors made less favorable judgments about ethnic minority students’ competence ( Glock and Kleen, 2021 ).…”
Section: Causal Attributions In the Educational Contextmentioning
confidence: 98%
See 3 more Smart Citations